2012
DOI: 10.1007/s11745-012-3729-3
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat Composition Influences Tissue Lipid Profile and Gene Expression in Fischer‐344 Rats

Abstract: The AIN-76A diet causes fatty liver in rodents when fed for long periods of time. The aim of this study was to utilize fatty acid analysis and transcriptomics to investigate the effects of different fat sources in the AIN-76A diet on tissue lipid profiles and gene expression in male, weanling Fischer-344 rats. Animals were fed isocaloric diets that differed only in the fat source: (1) corn oil (CO) (2) anhydrous milk fat (AMF), and (3) AMF supplemented with 10% phospholipids from the milk fat globule membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 35 publications
(39 reference statements)
3
19
0
Order By: Relevance
“…The results from our current study are in accord with previous animal studies that showed fewer adverse effects on plasma lipids by MFGM or its components (17)(18)(19)(20)(21)(22) than with other milk fats. Note that the current differences between the 2 milkfat diets in regard to lipoprotein response occurred despite high intakes of SFA.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results from our current study are in accord with previous animal studies that showed fewer adverse effects on plasma lipids by MFGM or its components (17)(18)(19)(20)(21)(22) than with other milk fats. Note that the current differences between the 2 milkfat diets in regard to lipoprotein response occurred despite high intakes of SFA.…”
Section: Discussionsupporting
confidence: 92%
“…Some of these effects have also been associated with hepatic accumulation of phospholipids (33). Besides the effects on hepatic gene expression, milk phospholipids also seem to effect the partitioning of lipids in classes both within and between organs (17). Although data from the current study did not show a differential effect on plasma cholesterol mediated by differences in cholesterol synthesis or absorption, as assessed by the surrogate markers lathosterol, sitosterol, and campesterol, this possibility cannot be excluded until more-direct measurements in humans have been performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumption of fish oil significantly increased EPA and n-3 docosapentaenoic acid (DPA) in liver PL of male rats [6]. On the other side, the milk-fat-based diet which had both, significant contributions of saturated fatty acids (SFA) and low PUFA content, also reflected on plasma and tissue FA composition in rats [7]. …”
Section: Introductionmentioning
confidence: 99%
“…In mice, 2 wt% of a ''dairy PL-rich extract'' (containing PLs as a milk fat globule membrane isolate), added to a 21 wt% fat diet containing 0.15 wt% cholesterol, reduced liver and plasma lipids (14). Rats fed during 12 wk with an anhydrous milk fat diet supplemented with 10% of MPLs, compared with an anhydrous milk fat diet only, had more plasma TGs and PLs but less hepatic cholesterol esters (15). Moreover, 2 studies investigated the ability of milk sphingomyelin to inhibit intestinal absorption of cholesterol (16,17).…”
Section: Introductionmentioning
confidence: 99%